A Clinical Case Report: Atipical Ocular Albinism in a Dark Skin Patient - Buque, Amelia; Khalau, Sidonia (European Journal of Applied Sciences, 2023)
Aim: To report a clinical case of 22 years old male, with low visual acuity in both eyes. Methods: This case report is a retrospective and descriptive study. Data was gathered from patient clinical record file that included anamnesis, examination and analysis of diagnostic tests. Results: A 22 years old male, dark skin complains of headache, blurry visual acuity in his both eyes since childhood. Uncorrected visual acuity RE was 2/60 and 1/60 in the left. Best corrected vision 6/36 for the right eye and 6/60 for the left eye. Both eyes examination revealed horizontal nistagmus, iris well pigmented (brown dark). Both eye posterior segment exams revealed Albinotic fundus, both eyes hypo pigmented fundus with clear visualization of choroidal vessels. The macula and disc coherence tomography (OCT) reveled thickness, and anomalies. Conclusion: The albinism results in a generalized decrease in the pigmentation of the appendages, skin, hair and eyes. A rare genetic disease, albinism is globally characterized by specific deficits of the visual system associated with a variable hypo pigmentation. Other eye abnormalities associated with this condition include rapid, involuntary eye movements (nystagmus). This case has shown rare condition of ocular albinism. The physical changes where in fundus finding, nystagmus and permanent low vision acuity. The patient had no changes of dark skin, black hair, and dark